PENATALAKSANAAN PADA LAKI-LAKI USIA 22 TAHUN DENGAN PENYAKIT GASTROESOFAGEAL REFLUX DISEASE (GERD) MELALUI PENDEKATAN KEDOKTERAN KELUARGA DI PUSKESMAS GEDONG TATAAN - Arrizky, Muhammad Heickal Ikhlasul Amal; Saftarina, Fitria (CV. Jasa Sukses Abadi, 2024)
Gastroesophageal Reflux Disease (GERD) is a medical condition where stomach acid rises into the esophagus, with primary symptoms such as heartburn, regurgitation, chest pain, chronic cough, and hoarseness. GERD occurs due to the weakness of the valve between the stomach and esophagus. According to Riskesdas 2018, the prevalence of GERD in Indonesia is 40.8%, making it a significant health issue. Family doctor services that are oriented towards evidence-based medicine focus on identifying risk factors, clinical issues, and patient management through an approach that actively involves the patient and their family. This study used primary data through anamnesis, physical examination, and home visits to assess the environmental conditions that may impact the patient’s health. The assessment was done holistically, covering diagnosis, process, and research results both qualitatively and quantitatively. Indicators evaluated include diet, stress levels, adherence to therapy, physical activity, and environmental factors such as home cleanliness and access to healthcare. Before the intervention, the patient and family had limited knowledge about GERD, with unhealthy eating habits, such as irregular meals, overeating in one sitting, minimal intake of fruits and vegetables, and lack of exercise. After the intervention, the knowledge score increased from 4 in the pre-test to 9 in the post-test, indicating improved understanding of GERD and preventive measures. The holistic approach proved effective in improving the patient’s understanding, attitude, and behavior, as evidenced by improvements in the diagnostic evaluation at the end of the study.